The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.12659/msm.905107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stent-Assisted Coil Placement and Coiling-Only for the Treatment of Ruptured Intracranial Aneurysms

Abstract: BackgroundThe use of a stent during the acute post-hemorrhage period is controversial. We conducted a retrospective analysis on the clinical and angiographic outcomes of the ruptured aneurysms that were embolized with stent-assisted coiling or coiling-only.Material/MethodsWe reviewed data of 279 patients with 279 ruptured intracranial aneurysms who underwent coil embolization between July 2004 and June 2015. The baseline data on age, sex, medical history, aneurysm size, location, and Hunt and Hess grade were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This complication is not rare in the treatment of acutely ruptured aneurysms. Our finding is similar to previous studies that showed the incidence of thromboembolic complications was 7.8-15% after SAC of ruptured intracranial aneurysms (14)(15)(16)(17). Bsat et al ( 18) systematically reviewed the literature on SAC of acutely ruptured aneurysms in 1,582 patients and found that the overall rate of thromboembolic complications was 9.1% (95% CI: 6.0-12.7%; I = 72.8%).…”
Section: Discussionsupporting
confidence: 91%
“…This complication is not rare in the treatment of acutely ruptured aneurysms. Our finding is similar to previous studies that showed the incidence of thromboembolic complications was 7.8-15% after SAC of ruptured intracranial aneurysms (14)(15)(16)(17). Bsat et al ( 18) systematically reviewed the literature on SAC of acutely ruptured aneurysms in 1,582 patients and found that the overall rate of thromboembolic complications was 9.1% (95% CI: 6.0-12.7%; I = 72.8%).…”
Section: Discussionsupporting
confidence: 91%
“…23 In a similarly designed study, Liu et al reported an 11.5% complication rate for the SAC group vs a 9.0% complication rate for the non-SAC group that were treated for ruptured wide-necked aneurysms, but also found that the SAC group had 100% complete occlusion rate at follow-up vs a 53.8% complete occlusion rate for the non-SAC group, suggesting that stent-assisted coiling is associated with more durable coiling than coiling alone despite having a higher complication rate. 30 We report in our review that 73.6% of the 942 patients that underwent radiologic follow-up had stable or improved radiologic findings.…”
Section: Discussionmentioning
confidence: 78%
“…Non-specific thromboembolic events were the most common thromboembolic complication while intra-procedure re-rupture was the most common hemorrhagic complication. 13 Retrospective 2010 42 0.7 Gao et al 14 Retrospective 2011 232 1.0 Kung et al 15 Retrospective 2011 131 0.8 Lodi et al 16 Retrospective 2011 22 0.7 Amenta et al 17 Retrospective 2012 65 0.8 Golshani et al 18 Retrospective 2012 36 0.8 Alurkar et al 18 Retrospective 2012 42 0.8 Santillan et al 19 Retrospective 2012 20 0.6 Li et al 20 Retrospective 2013 19 0.6 Giyek et al 21 Retrospective 2013 70 0.9 Chung et al 22 Retrospective 2014 72 0.8 Bechan et al 23 Prospective 2015 45 0.9 Li et al 24 Retrospective 2015 38 0.7 Yang et al 25 Retrospective 2015 211 0.8 Cai et al 26 Retrospective 2016 65 0.8 Zhao et al 27 Retrospective 2016 23 1.0 Muto et al 28 Retrospective 2016 40 0.7 Liu et al 29 Retrospective 2016 218 0.9 Liu et al 30 Retrospective 2017 113 0.9 Ho et al 31 Retrospective 2018 29 0.8 Zuo et al 32 Retrospective 2018 133 1.0 Roh et al 33 Retrospective 2019 38 0.8 Kim et al 34 Retrospective 2019 11 0.7 *Each article was assigned a quality score to stratify them based on risk of heterogeneity, 0 being high risk and 1 being low risk. Other hemorrhagic complications: 14 (9.5%) Infarction: 7 (4.6%)…”
Section: Resultsmentioning
confidence: 99%
“…With the advances in neuroimaging and endovascular devices, several recent studies corroborated comparable effectiveness and better prognosis when using endovascular treatment as compared to microsurgical clipping (5,6) for ruptured tiny intracranial aneurysms. Simultaneously, previous studies indicated that the stent-assisted coiling (SAC) technique was associated with a higher complete occlusion rate and lower recurrence rate at follow-up compared with coiling alone (CA) in ruptured intracranial aneurysms (7,8). However, studies on aneurysm occlusion, recurrence, and procedural complication rates of SAC treatment for ruptured tiny intracranial aneurysms were limited and heterogeneous (9, 10).…”
Section: Introductionmentioning
confidence: 99%